Bank rescues and bailout expectations: The erosion of market discipline during the financial crisis - Florian Hett; Alexander Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We design a novel test for changes in market discipline based on the relation between firm-specific risk, credit spreads, and equity returns. We use our method to analyze the evolution of bailout expectations during the recent financial crisis. We find that bailout expectations peaked in reaction to government interventions following the failure of Lehman Brothers, and returned to pre-crisis levels following the initiation of the Dodd-Frank Act. We do not find such changes in market discipline for non-financial firms. Finally, market discipline is weaker for government-sponsored enterprises (GSEs) and systemically important banks (SIBs) than for investment banks.
Keywords: 330